Forest fire occurrence increases the distribution of a scarce forest type in the Mediterranean Basin - Arnan, Xavier; Quevedo, Lídia; Rodrigo, Anselm (Acta Oecologica, 2013)
Here we report how ﬁre recurrence increases the distribution of a scarce forest type in NE Spain that is dominated by the resprouter tree species Arbutus unedo. We used a combination of GIS and ﬁeld surveys to determine the effect of ﬁre and pre-ﬁre vegetation on the appearance of A. unedo forests. In the ﬁeld, we also analyzed the factors that promote ﬁre and lead to the appearance of A. unedo forests. Our results reveal an increased occurrence of A. unedo forests in NE Spain in recent years; this phenomenon was strongly related to ﬁre recurrence and the vegetation type present prior to ﬁre. Most Pinus halepensis forests that burned more than once gave rise to A. unedo forests. Our results indicate that these conversions were related to a reduction in pine density coupled with increases in the density and size of A. unedo trees due to recurrent ﬁres. Given that ﬁres are increasing in number and magnitude in the Mediterranean, we predict a major change in landscape structure and composition at the regional scale
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: Arbutus unedo; Forest dominance; GIS analysis; Mediterranean; Pinus halepensis; Wildﬁres

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Post-fire recovery of Mediterranean ground ant communities follows vegetation and dryness gradients - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Biogeography, 2006)
Aim In the Mediterranean Basin, the main forest communities vary in their ability to recover after ﬁre. In this study we analyse the effects of ﬁre on ant communities occurring in various vegetation types distributed along a geographical gradient in the western Mediterranean region. Location The study was carried out in burned and unburned habitats of 22 sites corresponding to eight vegetation types distributed along a gradient of dryness throughout Catalonia (north-east Spain). Methods We placed ﬁve pairs of plots (one plot located in the burned area and the second one placed in the unburned margin) per site. We compared ant communities in these unburned and burned plot types 8 years after ﬁre using pitfall traps. Traps were set out in mid-May and mid-July. We analysed the structure and composition of ant communities in the burned and unburned areas of these vegetation types using anova tests, correspondence analysis (CA) and linear regression. Results The resilience of ant communities varies with vegetation type. Ant communities in forests with high resilience also recover rapidly after ﬁre, while those in forests that do not recover after ﬁre show the lowest resilience. Species richness does not depend on burning or vegetation type. The resilience of these Mediterranean ant communities to ﬁre is related to the environmental characteristics of the region where they live. Accordingly, differences between burned and unburned habitats are smaller for ant communities in areas with higher water deﬁcit in summer than for those in moister ones. Main conclusions The structure and composition of ant communities after ﬁre depends on the level of direct mortality caused by the ﬁre. It affects ant species differently, as determined by the habitats used for nesting and foraging. The reestablishment of vegetation cover depends on forest composition before the ﬁre. As vegetation cover determines resource and microhabitat availability and competitive relationships among species, forest composition before the ﬁre also affects post-ﬁre recovery of ant communities to the medium-term. Finally, ant communities living in drier areas recover more quickly after ﬁre than those living in moister ones. This pattern might be because in areas with higher water deﬁcit there are more species characteristic of open environments, which are habitats similar to those generated after ﬁre.
Keywords: Ants; diversity; dryness gradient; forest type; Mediterranean communities; post-ﬁre recovery; resilience; Species richness; ﬁre

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Broncano, Maria José; Retana, Javier; Rodrigo, Anselm (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.
Keywords: burn severity; mediterranean forest; natural regeneration; post-fire recovery; resilience

Predicting the Recovery of Pinus halepensis and Quercus ilex Forests after a Large Wildfire in Northeastern Spain - Broncano, Maria José; Retana, Javier; Rodrigo, Anselm (Plant Ecology, 2005)
Quercus ilex and Pinus halepensis are two of the most common tree species of the western Mediterranean basin. Both species regenerate reliably after ﬁre: P. halepensis colonizes recently disturbed areas by eﬀective seedling recruitment, while Q. ilex resprouts vigorously after disturbances. For this reason, the natural regeneration of these species after ﬁre should ensure the re-establishment of a forest similar to that which existed before the ﬁre. This study analyzes with a simple simulation model whether or not the relative abundance of monospeciﬁc and mixed forests of these species in the landscape is altered by ﬁre. We also analyze the topographic factors and the forest structure before the ﬁre that determine the changes in forest composition after ﬁre. This study has been carried out in a large ﬁre that occurred in NE Spain. Overall, 33% of plots changed to another community type, but this probability of change varied considerably among community types before the ﬁre. Monospeciﬁc forests of P. halepensis or Q. ilex had a high probability of remaining in their original composition after the ﬁre, whereas the resilience of mixed forests of these two species was quite low. Mixed forests changed for the most part to monospeciﬁc P. halepensis or Q. ilex forests. Analysis of several factors determining these changes indicated that only elevation as a signiﬁcant topographical variable. The eﬀect of ﬁre was to increase the altitudinal diﬀerentiation between the two species. P. halepensis forests that changed to mixed or Q. ilex forests were those of highest elevation, while the mixed and Q. ilex plots that changed to P. halepensis forests were those located at the lowest elevations. Concerning structural variables before ﬁre, density of Q. ilex trees before the ﬁre showed a much greater eﬀect than P. halepensis density in determining the post-ﬁre community. Finally, burn severity also inﬂuenced the changes observed. For both P. halepensis and Q. ilex forests, plots that changed to another forest type were mainly those that burned more severely. In the case of mixed forests, even low ﬁre severities involved high probabilities of change to monospeciﬁc forests.
Keywords: burn severity; mediterranean forest; natural regeneration; post-fire recovery; resilience

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall

Nitrogen circulation in a Mediterranean holm oak forest, La Castanya, Montseny, northeastern Spain - Avila, Anna; Rodrigo, Anselm; Rodà, Ferran (Hydrology and Earth System …, 2002)
Bulk deposition, wet-only deposition, throughfall and dry deposition inferred from washing foliage and surrogate surfaces were used to describe inorganic N inputs to a forested catchment in the Montseny Mountains (La Castanya, Catalonia, Spain). Bulk inputs of inorganic N were moderate, with a mean of 5.7 kg N ha -1 yr -1 , ranging between 4 and 10 kg N ha -1 yr -1 for the period 1983 to 2000. Dry deposition fluxes estimated from washing branches added about 9 kg N ha -1 yr -1 to wet inputs and the total atmospheric deposition was estimated in 15 kg N ha -1 yr -1 . Despite this substantial input flux, nearly all the inorganic nitrogen was retained within the forest ecosystem: NH4 + and NO3 - concentrations decreased dramatically as water crossed the canopy and the soil profile. In the stream, at baseflow conditions, NH4 + and NO3 - concentrations were always below the analytical detection limit (< 2 µeq L -1 ). Only briefly during peak flows did NO3 - concentrations increase up to 100 µeq L -1 . Averaged over 10 years (1984-1994), the export of N at the catchment outlet was 0.05 kg N ha -1 yr -1 . This indicates a very tight N cycling allowing for an increase of N availability in these undisturbed forest ecosystems.
Keywords: ammonium; bulk deposition; Dry deposition; la castanya; montseny; nitrate; soil water; Spain; throughfall